Subject Orientation of Teaching and Academic Subjects in the Context of Different Didactic Approaches - I. M. Osmolovskaya (Образование и наука)
The paper is devoted to the research findings concerning the didactic characteristics and means of subject-oriented teaching. The research question includes the content of the general secondary education regarded as the design object. The process of selecting and structuring materials is reviewed from the theoretical standpoint, and the attempt is made to identify the ways of selecting materials for students’ learning from the social experience reflected in culture. The author introduces the concept of subject-orientation as a tool providing pedagogic adaptation of social experience in the process of teaching content development. Subject-oriented teaching is defined in the context of traditional knowledge, as well as the competence and student-oriented didac- tic approaches; the forms and means of its realization being indicated providing the new ways for introducing and understanding the educational subject. The research results can be used by the specialists in didactic, curricula developers, authors of textbooks in various subjects.